Modelling of optical emissions enhanced by the HF pumping of the ionospheric F-region - T. Sergienko; B. Gustavsson; U. Brändström; K. Axelsson (Annales Geophysicae, 2012)
Strong enhancement of the optical emissions with excitation threshold from 1.96 eV (630.0 nm from O( 1 D)) up to 18.75 eV (427.8 nm from N 2 + (1NG)) have been observed during experiments of the ionosphere modification by high power HF radio waves. Analysis of the optical emission ratios showed clearly that a significant part of the ionospheric electrons have to be accelerated to energies above 30 eV and more in the region where the HF radio wave effectively interacts with the ionospheric plasma. The Monte-Carlo model of electron transport and the optical emission model were used to study the dependence of the optical emission intensity on the acceleration electron parameters. We obtained the following results from analysis of the enhanced intensities of the four optical emissions (630.0, 557.7, 844.6 and 427.8 nm) observed in the EISCAT heating experiment on 10 March 2002. The 630.0 emission with an excitation threshold of 1.96 eV is formed predominately by the thermal electrons, where the accelerated electrons play a minor role in the excitation of this emission. In order to explain the experimentally observed intensity ratios, the accelerated electrons must gain energies of more than 60 eV. For accelerated electrons with a power law energy dependence, the efficiency of the optical emission excitation depends on the exponent defining the shape of the electron spectra. However, an agreement with the observed emission intensities is achieved for exponent values not less than zero. Moreover, increasing the exponent to higher values does not affect the emission intensity ratios.